2021
DOI: 10.1038/s41380-021-01075-4
|View full text |Cite
|
Sign up to set email alerts
|

Habitual coffee drinkers display a distinct pattern of brain functional connectivity

Abstract: Coffee is the most widely consumed source of caffeine worldwide, partly due to the psychoactive effects of this methylxanthine. Interestingly, the effects of its chronic consumption on the brain’s intrinsic functional networks are still largely unknown. This study provides the first extended characterization of the effects of chronic coffee consumption on human brain networks. Subjects were recruited and divided into two groups: habitual coffee drinkers (CD) and non-coffee drinkers (NCD). Resting-state functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 57 publications
(76 reference statements)
3
21
0
1
Order By: Relevance
“…Based on the actions of caffeine, it is plausible that the stimulatory effects of caffeine might directly lead to the reorganization of network properties toward a state of increased efficiency. A recent fMRI study showed that habitual coffee drinkers had distinct brain FC properties from non-coffee drinkers, which could support our speculation 33 . Further studies are needed to unveil the mechanisms underlying the changes in network properties after coffee consumption.…”
Section: Discussionsupporting
confidence: 85%
“…Based on the actions of caffeine, it is plausible that the stimulatory effects of caffeine might directly lead to the reorganization of network properties toward a state of increased efficiency. A recent fMRI study showed that habitual coffee drinkers had distinct brain FC properties from non-coffee drinkers, which could support our speculation 33 . Further studies are needed to unveil the mechanisms underlying the changes in network properties after coffee consumption.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the known potential side effects of coffee, where high doses (more than 400mg, cf. EFSA [4]) not only exceed the beneficial ceiling that has been reported as effective for certain performance purposes but may also negatively affect the very concerns caffeine is aimed to address (e.g., increasing anxiety [3]), there is a general reliance on drinking coffee, more than, for instance, on using medicines or food supplements for similar purposes. Among other aspects, the broad acceptance of such a daily consumption practice is linked to its ambivalent social status, as both a substance with pharmacological properties and a common beverage both inside and outside work.…”
Section: Resultsmentioning
confidence: 99%
“…Besides being a socially rooted drink, coffee's main bioactive compound (caffeine) is claimed to have cognitive enhancing properties associated with fatigue reduction and improvement of mental alertness, concentration, and short-term memory, amongst other performative effects and benefits [2]. Yet, the effect of chronic coffee consumption on the brain is currently starting to be studied [3]. In a context of increasingly competitive economies, where the work rhythms and performance demands are extremely high in many professional environments, what is the role of coffee in managing everyday imperatives at work?…”
Section: Introductionmentioning
confidence: 99%
“…Particularly relevant to this study is the finding that females were more susceptible to the anxiogenic effects of caffeine under the same dose than males (Domschke et al, 2012;Gajewska et al, 2013). In comparison, a study examining the resting functional connectivity between habitual and non-coffee drinkers found an association between the increased frequency of caffeine consumption and anxiety in males only (Magalhães et al, 2021).…”
Section: Are Caffeine Effects On Memory Different In Males and Females?mentioning
confidence: 87%
“…Although we did not focus on neuroimaging findings, in studies reviewed there is also evidence that an acute dose of caffeine is related to activation of attentional networks, such as bilateral medial frontopolar cortex extending to anterior cingulate gyrus (Koppelstaetter et al, 2008), bilateral dorsolateral prefrontal cortex (PFC), and the left thalamus (Haller et al, 2017(Haller et al, , 2013Klaassen et al, 2013). Furthermore, lifelong habitual caffeine consumers compared to non-coffee drinkers showed increased functional connectivity between cerebellar and several subcortical areas known to be involved in attention, arousal, and memory acquisition, including the thalamus, lingual and inferior occipital gyrus, and parahippocampus (Magalhães et al, 2021). In electroencephalography studies, caffeine is associated with increased prestimulus alpha amplitude (Trunk et al, 2015), and an increase in the theta activity in the right PFC, central, and temporal areas (Ueda and Nakao, 2019).…”
Section: Drug Mechanismsmentioning
confidence: 99%